Philosophy of technology : an introduction for technology and business students /: an introduction for technology and business students. (2015) - Verkerk, Maarten Johannes, 1953-; Hoogland, J (Jan); Stoep, J. van der (Jan); Vries, Marc J. de, 1958-
No abstract available